(untitled) (Journal of Fatima Jinnah Medical University, 2022)
Background: Paraphenylene diamine (commonly known as Kala Pathar in Pakistan) poisoning is a common presentation in adults as well as pediatric patients in Southern Punjab. The study was carried out to assess paraphenylene diamine poisoning in pediatric cases. Patients and methods: The cross-sectional study was carried out at Bahawal Victoria Hospital Bahawalpur. All the pediatric cases (<15 years age) of paraphenylene diamine poisoning reported during April 2021 to April 2022. Data was entered and analyzed in SPSS. Results: Total 84 children presented at pediatric department of the hospital. Out of these, 43 (51.2%) were males and 41 (48.8%) were females. Age range was between 02 months and 15 years, mean age being 9.4 + 4.49 years. Majority of cases (46.6%) ingested paraphenylene diamine accidentally, followed by suicidal intention (29.8%), homicidal intent (21.4%) and unknown motive in 2.4% cases. Of all, 49 (58.3%) died of poisoning and 35 (41.7%) survived. Of all the cases, 44 (52.4%) underwent emergency tracheostomy. Conclusions: Paraphenylene diamine poisoning in children is an alarming trend. Although majority of the cases ingested it accidently but intake due to suicidal or homicidal reason were also high. Positive outcome was associated with higher age, carrying out early tracheostomy and mode of poisoning (homicidal cases had poorest outcome whereas accidental and suicidal pediatric cases had more chances of survival).